Impact of the COVID-19 Global Pandemic on the Otolaryngology Fellowship Application Process. (October 2020) - Nesemeier, B. Ryan; Lebo, Nicole L.; Schmalbach, Cecelia E.; Barnes, Kaitlyn J.; Vernon, Dominic; Ting, Jonathan Y.; Shipchandler, Taha Z.
On March 11, 2020, the World Health Organization declared coronavirus disease 2019 a global pandemic. In addition to massive social disruption, this pandemic affected the traditional fellowship interview season for otolaryngology subspecialties, including head and neck surgical oncology, facial plastic and reconstructive surgery, laryngology, rhinology, neurotology, and pediatric otolaryngology. The impact on the fellowship interview process, from the standpoint of the institution and the applicant, necessitated the use of alternative interview processes. This change may alter the future of how interviews and the match proceed for years to come, with nontraditional methods of interviewing becoming a mainstay. While the impact this pandemic has on the fellowship match process is not yet fully realized, this commentary aims to discuss the challenges faced on both sides of the equation and to offer solutions during these unprecedented times.